Unified Approach for the Total Synthesis of Bis-THF C15 Acetogenins: A Chloroenyne from Laurencia majuscula, Laurendecumenyne B and Laurefurenynes A/B - Senapati, Sibadatta; Unmesh, Nivedya A.; Shet, Manoj N.; Ahmad, Iram; Ajikumar, Nandu; Ramana, Chepuri V. (Synthesis, 2021)
A highly diastereoselective total synthesis of several bis-THF C15 acetogenin natural products, chloroenyne from Laurencia majuscula, laurendecumenyne B, and laurefurenynes A/B, is reported. Additionally the synthesis of an advanced intermediate reported in the earlier total synthesis of (E/Z)-elatenynes (formal synthesis) is described. The salient features in the synthesis include epoxide opening, Birch reduction, Sharpless asymmetric dihydroxylation-cycloetherification, SN2 halogenation, and a relay cross metathesis.
Keywords: bis-THF C15 acetogenins; carbohydrate building block; Sharpless asymmetric dihydroxylation-cycloetherification; SN2 halogenation; relay-cross-metathesis